Order Management in the Era of Customization - A. V. Netievsky; M. A. Prilutskaya (Управленческие науки)
The economic growth and development of the country largely depends on success in the main industries, where mechanical engineering plays a key role. The economies of different countries rely on industrial enterprises that satisfy people’s needs through the production of goods and services. To ensure competitiveness in a dynamically changing market, continuous improvement and development of enterprises is required. In the current conditions, mechanical engineering enterprises increasingly need to adapt to each individual customer, which in turn forces them to rebuild enterprises to the parameters typical for single or small-scale production. The production process is the joint work of tools, equipment and personnel through which products are produced. The complexity of the process of releasing new products is due to the involvement of a large number of departments involved in this process. Order execution is based primarily on the management of production systems. One of the most important processes in enterprise management is the order management process.The purpose of this study is to determine the methods of optimizing the order management process and reducing the influence of the internal cooperation factor on the increase of the period of its implementation at machine-building enterprises. As a methodological basis such general scientific methods as analysis, synthesis, comparison and contrast were used. As the information base, the article analyzes the works of modern authors who consider the issues of order management and such an element of the organizational structure as internal cooperation between departments, their influence on the internal processes of the enterprise and the timing of order execution. The features of the planning process for a single type of production are considered. In the course of the work, the main reasons for the shift in previously determined order completion dates, the most important indicators for order fulfillment, the peculiarities of the planning process at the unit type of production were considered, as well as the most frequently encountered problems during project implementation were identified. In connection with the trend towards changes and development of enterprises, in terms of changes in order management processes for customized products, an increase in the number of created enterprises and an increase in the share of customized products, a conclusion was made about the relevance of studying the order management process in a single type of production at machine-building enterprises. Conclusions are drawn about the need for further study of the issues under consideration. The materials can be used in companies in the real sector of the economy, in administrative structures and in the educational process.